Mundialização e subordinação: o Brasil, o movimento do capital e as cadeias globais de valor - Lacerda, Franklin de Oliveira (2017)
In 1985, Brazilian industry experienced its peak, accounting approximately for 25% of the value added to GDP. This participation, however, has been falling steadily ever since and currently corresponds to 15%. This loss of importance of the industry raises several doubts and challenges, once since 1930 the industrialization process is present in the debates on economic development in periphery countries, including Brazil. This deindustrialization movement seems to be related to the Brazilian choice for industrialization through transnational capital. This choice did not take into account the fact that this capital has its own accumulation movement, which implies in global processes of restructuring and occupation of national spaces. This capital travels around the world according to its strategy of accumulation, which can result in deindustrialization processes. Since the mid-1980s, as a result of the liberalization of trade, finance and capital flows, as well as technological advances achieved in telecommunications and information systems, capital has undergone processes of restructuring and new forms of productive organization in space, Constituting new global value chains (GVC). The strategies of industrialization through import substitution and export oriented industrialization seem not to have the same relevance that they had in the past, since the new GVCs decentralized the production chains in different countries, according to the strategies of each individual capital (economic groups), now acting Globally. In this scenario, the present work seeks to analyze the situation of the Brazilian industry to understand its evolution in the last decades and to outline its new position in the GVCs in front of this movement of capital relocation, according to its global strategy